A Community's Knowledge and Attitude in Recognizing Symptoms and Diarrhea Management in Children - Arina Dery Puspitasari; Novitri Wulandari; Bindaria Mutmaina Prabawati; Liza Yudistira Yusan (Universitas Airlangga, 2022)
Background: Diarrhea is the world's second-biggest cause of death among children. Children suffer from severe dehydration due to the lack of understanding of treating diarrhea properly. Objective: This study aimed to assess the level of community knowledge and attitudes toward the treatment of diarrhea in children. Methods: This was an observational, cross-sectional study conducted in a community in Gresik, Indonesia, in 2019. A Likert scale questionnaire, consisting of 10 items on knowledge and five on community attitudes on diarrhea management in children, was used to collect data. Results: One hundred and seven participants responded to the survey, and 89.72% were women. 'Respondents' mean age was 41.84 ± 11.27 years with various levels of education. It was found that the community had good knowledge of diarrhea management in children, as shown by the finding that 84.11% of the participants provided the correct answers. About 87.85% of the participants were aware of the signs and symptoms of diarrhea in children. However, there is still a shortage of understanding about managing diarrhea properly, particularly when identifying the necessary medicine. About 89.72% of the participants demonstrated a